Informal economies in Bairro Alto (Lisbon): the nocturnal tourist city explained through a street dealer’s life story - Nofre, Jordi (Etnográfica, 2025)
The historical neighbourhood of Bairro Alto is the city’s most iconic nightlife destination, especially for tourists visiting Lisbon (Portugal). The expansion of commercial nightlife in this area has been accompanied by the increasing presence of informal economies in the public space during the hours of evening and night, specifically street vendors, and street drug dealers. Based on ethnographic immersion carried out between 2010 and 2020, this article presents the life story of a drug dealing gang leader who operates in a particular street in Bairro Alto. His life story demonstrates how street drug dealing in the Bairro Alto tourist nightlife constitutes a central strategy for the economic survival of John and his boys as well as an informal, alternative and effective mechanism of socioprofessional inclusion amidst a wider social reality highly characterized by class-based and ethnic-based institutional(ised) exclusion.